KOMUNIKASI PERSUASIF GURU DALAM MENSOSIALISASIKAN PENGGUNAAN PAKAIAN SYAR’I TERHADAP SISWA-SISWI DI MADRASAH ALIYAH PERSIAPAN NEGERI BESITANG - Lilis Handayani; Wahyu Ziaulhaq (LPPM STISIP Persada Bunda, 2022)
This study describes the persuasive communication of teachers in disseminating the use of syar'i clothing to students in the preparatory madrasah aliyah in Besitang. The purpose of this study is to educate students and readers to always wear clothes that are based on Islamic religious guidance. This type of research is a qualitative research that seeks to explain social phenomena that are developing in the current mass, from the results of this study it has been found that: First, it takes the role of parents of students to always give advice to their children so that they always prioritize dress etiquette. Second, madrasa teachers always provide education to students so that they cover their genitals when they are in the madrasa environment and in the community by using humanist and persuasive language. Third, madrasa teachers will give sanctions to students if they violate dress procedures when in the madrasa environment